1977
DOI: 10.1038/bjc.1977.31
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the role of smoking and chewing tobacco in oral, pharyngeal, and oesophageal cancers

Abstract: Summary.-Evidence is presented which indicates that S-(1,2,3,4-tetrahydro-2-hydroxy-l-naphthyl)-L-cysteine (THN-cysteine), formed by the reaction of 1,2-epoxy-THN with cysteine, can be incorporated into protein. The position of incorporation of THN-cysteine into protein would depend on whether the epoxide of THN reacts with cysteinyl-tRNACYs or with cysteine. In both cases, the mechanism of incorporation of THN-cysteine into protein is the same as for the natural amino acids. For example, the incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0
1

Year Published

1981
1981
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 11 publications
6
60
0
1
Order By: Relevance
“…Many studies (Wynder et al, 1956;Feldman & Hazan, 1975;Jayant et al, 1977;Simarak et al, 1977;McMichael, 1978;Ward Hinds et al, 1979) Wynder et al (1976) showed that at each measure of cigarette consumption heavy alcohol consumption increased the risk of laryngeal cancer, but no such increased risk was seen in non-smoking heavy drinkers. The findings of Feldman & Hazan (1975) were similar, but a significant synergistic effect between tobacco and alcohol was not demonstrated.…”
Section: Combined Effect Of Tobacco and Alcohcmentioning
confidence: 99%
“…Many studies (Wynder et al, 1956;Feldman & Hazan, 1975;Jayant et al, 1977;Simarak et al, 1977;McMichael, 1978;Ward Hinds et al, 1979) Wynder et al (1976) showed that at each measure of cigarette consumption heavy alcohol consumption increased the risk of laryngeal cancer, but no such increased risk was seen in non-smoking heavy drinkers. The findings of Feldman & Hazan (1975) were similar, but a significant synergistic effect between tobacco and alcohol was not demonstrated.…”
Section: Combined Effect Of Tobacco and Alcohcmentioning
confidence: 99%
“…The epidemiology of gingival carcinoma has been studied previously as part of a case spectrum consisting of other intra oral and head and neck cancers (Sanghvi et al, 1955;Shanta & Krishnamoorthy, 1959, 1963Wahi et al, 1965;Jussawalla & Deshpande, 1971;Jayant et al, 1977: Notani, 1988 Pan chewing, pan-tobacco chewing, bidi smoking, cigarette smoking, alcohol and nasal snuff inhalation were the habits ascertained for the cases and controls. Pan chewing is defined as chewing of a quid containing fresh betel leaves (Piper betle), arecanut (Areca catechu) and aqueous lime (calcium hydroxide).…”
mentioning
confidence: 99%
“…The epidemiology of gingival carcinoma has been studied previously as part of a case spectrum consisting of other intra oral and head and neck cancers (Sanghvi et al, 1955;Shanta & Krishnamoorthy, 1959, 1963Wahi et al, 1965;Jussawalla & Deshpande, 1971;Jayant et al, 1977: Notani, 1988Wynder et al, 1957;Winn et al, 1981. However, aetiology of cancers may vary from site to site within the oral cavity.…”
mentioning
confidence: 99%
“…As seen earlier, bidi smokers with or without the additional habit -of tobacco chewing have a much higher risk of cancer of the oropharynx including base of the tongue and larynx compared to cigarette smokers. Consequently, one could (Jayant et al, 1977). Even so, the change in cumulative incidence rate in successive cohorts is similar to the pattern observed for hypopharyngeal cancer.…”
Section: Methodsmentioning
confidence: 52%